1979
DOI: 10.1128/iai.26.3.791-794.1979
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to adjuvant-induced arthritis among germfree, specific-pathogen-free, and conventional rats

Abstract: Germfree F344 rats developed severe arthritis with 100% incidence after a single intradermal injection of either squalane containing 0.5 mg of heat-killed Mycobacterium bovis BCG or a water-in-oil emulsion containing 0.2 mg of peptidoglycan derived from Staphylococcus epidermidis. Conventional F344 rats developed less-severe arthritis with 20% incidence for heat-killed BCG and 0% incidence for peptidoglycan. Specific-pathogen-free rats showed an intermediate susceptibility between germfree and conventional rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(37 citation statements)
references
References 14 publications
3
33
0
Order By: Relevance
“…In a preliminary study, we observed that Fisher F344 rats raised in a barrier facility (BF) (BF-Fisher rats) were susceptihle to AA, whereas Fisher rats raised in a conventional (CV) facility (CV-Fisher rats) developed resistance to AA. A similar finding has previously been reported from another laboratory (82). In our study, upon transfer of BF-Fisher rats into a CV facility, these rats acquired resistance to AA within a few weeks.…”
Section: Bctd-specific T Cells + Recruitment Of Bctd/rctdcross-reactisupporting
confidence: 92%
“…In a preliminary study, we observed that Fisher F344 rats raised in a barrier facility (BF) (BF-Fisher rats) were susceptihle to AA, whereas Fisher rats raised in a conventional (CV) facility (CV-Fisher rats) developed resistance to AA. A similar finding has previously been reported from another laboratory (82). In our study, upon transfer of BF-Fisher rats into a CV facility, these rats acquired resistance to AA within a few weeks.…”
Section: Bctd-specific T Cells + Recruitment Of Bctd/rctdcross-reactisupporting
confidence: 92%
“…To pursue this matter, it seems very important to investigate whether or not germfree rats can develop adjuvant-induced arthritis. Pearson et al (33), and we in our previous paper (19), reported that adjuvant-induced arthritis can be induced in germfree and conventional rats with equal ease and suggested that the bacterial flora is not necessary for development of the disease and rather modulates the development of the disease, since germfree rats developed more severe disease than that in specific pathogen-free and conventional rats.…”
mentioning
confidence: 79%
“…The skin thickness was carefully recorded by measuring both ears with a spring-loaded type micrometer (Mitsutoyo Mfg. Co., Tokyo, Japan) at 24 and 48 hr for delayed-type hypersensitivity (9,19,22,25). In some experiments, sections of the ears were stained with hematoxylin and eosin after fixation with 10% formalin.…”
mentioning
confidence: 99%
“…The intestinal bacterial flora is known to play a role in modulation of an immune response and in experimental models of arthritis, as adjuvant-or streptococcal cell wall arthritis, disease severity may be modulated by alterations in the bowel flora [1][2][3]. In the human disease rheumatoid arthritis (RA) an involvement of the bowel flora has been suggested in the aetiology, although no conclusive evidence for this is at present available [4].…”
Section: Introductionmentioning
confidence: 99%